The Effect of a Hybrid Work Environment on Employee Performance with Motivation as a Moderating Variable at the Department of Manpower, Cooperatives, and Micro, Small, and Medium Enterprises of Serdang Bedagai Regency - Irpan Hariono Saragih; Hernawaty; Erwansyah (CV. Doki Course and Training, 2026)
This study aims to analyze the effect of a hybrid work environment on employee performance with work motivation as a moderating variable at the Department of Manpower, Cooperatives, Small and Medium Enterprises of Serdang Bedagai Regency. This research employed a quantitative associative approach. The population consisted of 35 employees, and a saturated sampling technique was applied. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results show that the hybrid work environment does not have a significant effect on employee performance, as indicated by a T-statistic value of 1.149 and a p-value of 0.258, leading to the rejection of the first hypothesis. Work motivation also does not have a significant effect on employee performance, with a T-statistic of 1.839 and a p-value of 0.074, resulting in the rejection of the second hypothesis. Furthermore, work motivation does not moderate the relationship between the hybrid work environment and employee performance, as shown by a T-statistic of 1.082 and a p-value of 0.287, so the third hypothesis is also rejected. Based on these findings, it is recommended that government institutions do not rely solely on hybrid work systems to improve employee performance, but also strengthen supporting factors such as digital competence, performance supervision, task clarity, and organizational policies that align with job characteristics.